Herança genética da resistência a Fusarium verticillioides e estudo de associação genômica para resistência ao Complexo Tar Spot em milho - Vieira, Paula Mikaely Henrique (2019)
Fusarium verticillioides fungi and the tar spot complex caused by the interaction of the fungi, Phyllachora maydis, Monographella maydis and Coniothyrium phyllachorae, have caused great damage to maize crops. The resistance to these pathogens is a quantitative trait and has a high environmental influence where obtain highly resistant cultivars is a major challenge for genetic improvement. In this context, the aim of this study were: i) Study the genetic inheritance of resistance to Fusarium verticillioides and the genetic variability available in the segregating population; ii) Identify progenies of the segregating population for resistance to F. verticillioides which present the best performance for productivity; iii) Identify, between two accessions with potential tar spot resistance, coming from the CIMMYT germplasm bank, which will best contribute to the introgression of resistance genes in elite materials, and identify the resistance-associated genes present in these accessions via GWAS. For the study of resistance to F. verticilliodes, it was used two lines previously identified as contrasting for resistance. From these were obtained the generations F1, F2:3, RC11 and RC12, they were sown in the 2017/2018 crop season applying the complete randomized block design with three replications. The artificial inoculation of the pathogen was made in the flowering period. The blotter test was used to phenotype the incidence and severity of the disease. For genotyping purposes, 11 previously obtained primers associated with resistance to F. verticillioides were tested. In the experiment for identification of resistant accessions to TSC, two accessions were crossed with four elite maize lines (CMLs) from the maize breeding program at CIMMYT. The F1 generation was obtained and was backcrossed with the recurrent parents, the CMLs. At the end, eight populations were generated. These were evaluated at two sites with high pathogen pressure, El Portillo, Mexico and Petén, Guatemala. The first phenotyping was performed two weeks after flowering, and then disease progression was assessed at two periods, 7 and 14 days after the first phenotyping. A bulk sample from the semi-inbred lines BC1S1 and BC1S2 for each population was obtained. The genotyping was performed using the DArT-Seq platform. A total of 8,401 SNPs were used for GWAS. For both experiments the phenotypic analysis was performed using a grade scale. The genetic and environmental variances, heritability and accuracy were calculated. The inheritance study of resistance to F. verticillioides shown that the parents were not totally contrasting. It was observed that there is variability for the segregating population and that it can be used for breeding. The gain with the selection was -0.70. The progenies 61 and 69 had better performance for both resistance and productivity. In the second experiment we observed that the GUAT153 accession presented better phenotypic performance, and that GUAT153 and OAXA280 presented different genes, not observed in the CMLs. Eleven small-effect SNPs involved in the resistance response to TSC were identified. The accessions carrying these alleles will be useful in the introgression of resistance alleles in elite germoplasm, and will contribute to the resistance background, allowing a lasting resistance of the improved genotypes.